2007
DOI: 10.1038/sj.cdd.4402283
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expansion of the tumorigenic lung cancer stem cell population

Abstract: Lung carcinoma is often incurable and remains the leading cancer killer in both men and women. Recent evidence indicates that tumors contain a small population of cancer stem cells that are responsible for tumor maintenance and spreading. The identification of the tumorigenic population that sustains lung cancer may contribute significantly to the development of effective therapies. Here, we found that the tumorigenic cells in small cell and non-small cell lung cancer are a rare population of undifferentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

39
1,265
5
24

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,495 publications
(1,333 citation statements)
references
References 26 publications
39
1,265
5
24
Order By: Relevance
“…[5][6][7][8][9] As shown in Figure 1b, all cell lines generated tumorospheres, and flow cytometry analyses showed that CD44 þ CD24 À population was highly enriched in tumorospheres (Supplementary Figure S1A). We sorted CD44 þ CD24 À cells from spheres of prostate and breast cancer using fluorescence-activated cell sorting (FACS) and achieved a purity of 495% as judged by postsorting flow analysis (Figure 1c).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…[5][6][7][8][9] As shown in Figure 1b, all cell lines generated tumorospheres, and flow cytometry analyses showed that CD44 þ CD24 À population was highly enriched in tumorospheres (Supplementary Figure S1A). We sorted CD44 þ CD24 À cells from spheres of prostate and breast cancer using fluorescence-activated cell sorting (FACS) and achieved a purity of 495% as judged by postsorting flow analysis (Figure 1c).…”
Section: Resultsmentioning
confidence: 89%
“…Collectively, our data suggest that both CSCs and spheres exhibited diverse stem cell-associated characteristics, consistent with previous reports. [5][6][7][8][9] CSCs overexpressed BAD with elevated phosphorylation. As CSCs are resistant to drugs 11 and phosphorylated BAD correlates with drug resistance in cancer patients, 25 we determined the level of BAD expression and phosphorylation in CSCs and tumorospheres.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] On the other hand, as the identification of tumorinitiating cells, also referred to as cancer stem cells, in acute myeloid leukemia, their presence has also been identified in a number of solid tumor types, such as breast, lung, ovarian, brain, and colon cancer. [12][13][14][15][16][17] Emerging evidence suggests that stem cells have a crucial role not only in the embryonic development and maintenance of mature normal tissues, but also in the development of malignancies and disease progression associated with poor prognosis. In fact, the expression of stem cell markers and their prognostic significance have been reported in several solid tumors, including colorectal cancer.…”
mentioning
confidence: 99%
“…[6][7][8][9][10] Eramo et al first demonstrated that CD133-positive lung cancer cells have the ability to self-renew and grow indefinitely as a tumor sphere. 11 In another study of small cell lung cancer (SCLC), Jiang et al demonstrated that SCLC cells with high CD133 levels had markedly enhanced tumorigenicity associated with the basic helixloop-helix transcription factor achaete-scute complex homolog 1. 12 In our previous study, we demonstrated that nonsmall cell lung cancer (NSCLC)-derived CD133-positive cells displayed higher octamer-binding transcription factor 4 (Oct-4) expression and possessed the ability to self-renew, potentially representing a reservoir of proliferative potential to generate lung cancer cells.…”
mentioning
confidence: 99%